Plan de mejoramiento para la empresa Racing Parts S.A., comercializadora de motocicletas, repuestos y taller multimarca, en la ciudad de Quito - Narváez Redrovan, Jonathan Mauricio (2016)
The marketing of motorcycles in our country has had a gradual growth since 2003 with a slight decrease in the last two years. Racing Parts Company S.A. has 4 years of experience in the Ecuadorian market, it points to the need for improvements to increase the existing customer base and maintaining long-term relationships with them. This document is an improvement plan that was developed to address the optimal performance of the company. PEST analysis management, evaluation matrix of external factors (EFE) and five forces of Porter to establish the factors that may affect the industry sales, maintenance and repair of motorcycles and related parts and accessories. Industry representing 1% of national GDP and generates superior resources to USD 300 million annually. Domestically diagnosis is use the SWOT matrix, SWOT weighted evaluation of internal factors (EFI), Boston Consulting Group (BCG) and impact and feasibility of strategies (IFA). By the matrices above evidence the need to invest company resources in critical areas for the line of business. Increased sales of new motorcycles and savings in operating costs: By obtaining the results of the analysis of both internal and external, improvements to be implemented, among which are prioritized identified. Each improvement has appropriate objectives and strategies to achieve improvements raised. The required investment will be $ 54.537,66, an amount that will be financed with 40% equity of the company and 60% by a credit managed in the Pacific Bank to 5 years with a rate of 11.83% per annum. The implementation of the improvement plan is viable with a NPV of $ 78.794,10 and an IRR of 62,40%.